Intrauterine inoculation of pseudorabies virus impairs mouse embryo implantation via inducing inflammation and apoptosis in endometrium - Chen, Zhiqiang; Wen, Yuting; Meng, Lizhou; Li, Suyao; Min, Wenpeng; Yuan, Anwen; Chang, Wen-Lin; Yang, Qing (Frontiers in Veterinary Science, 2024)
Pseudorabies virus (PRV) is the pathogenic agent of pseudorabies, causing serious reproductive failure in swine. However, it is still unknown whether PRV uterine inoculation impairs blastocyst implantation. In the present study, a PRV infection mouse model was developed. Pregnant mice were inoculated with either 104 or 105 50% tissue culture infectious dose (TCID50) units of PRV on gestation day 2 (GD2). Viral DNA was detected in tissues by PCR and/or in situ hybridization. Histopathological change and expression of proinflammatory cytokines in uterus were analyzed by H.E. staining and qPCR, respectively. Apoptosis was also investigated by TUNEL assay, and the expression of apoptosis-related proteins including Bax and Bcl-2 was detected by Western blot. The results showed that intrauterine exposure of PRV on GD2 reduced the number of embryo implantation site. Abundant viral DNA was detected in spinal marrow and brain, and small amounts of PRV genomes were detected in embryo implantation site, ovary as well as thymus. Considerable inflammatory cells infiltrating in the endometrium, with high levels of pro-inflammatory cytokines of interleukin (IL)-6, IL-1β and tumor necrosis factor-α mRNA after infection. In addition, PRV infection promoted apoptosis in stroma and endothelium of the mouse endometrium. Collectively, intrauterine inoculation of PRV during early pregnancy causes cytokine release syndrome and apoptosis in endometrium, which impairs mouse embryo implantation.